Crecimiento en una economía abierta: un marco de análisis para el Perú - Mendoza, Waldo (2000)
In this paper we present a review of the literature of economic growth for open economies. Then, from this review, we build a model of economic growth which take into account the main features of the Peruvian economy such as small economy, openness in goods and financia1 markets, strong link between imports and economic activity, exogenous technological change, exogenous financia1 capital inflows, importance of the externa1 constraint on the evolution of per capita gross domestic product (GDP) and the negative relationship between domestic saving and capital inflows. The model has two basic equations: the interna1 equilibrium equation and the externa1 equilibrium equation. The saving and investment equality determines per capita capital, and, given a production function, per capita GDP as well; while the equilibrium of the balance of payments determines real exchange rate. Thus this model allow us to show the effects of the interna1 factors such as rate of saving and propensity to import as well as the effects of the factors related to the international context such as exports and capital inflows on per capita capital (GDP) and real exchange rate.